The Grammar of Singapore English Used in Skype Conversation - M. Aries Taufiq (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
This article aims at investigating the grammar of conversation occurred among PT. BSI staffs and Cocomas Singapore (CMS) staffs. Since it was a cross cultural communication, the conversations were mostly taken place via Skype. Most of the time, CMS staffs used Singapore English (Singlish) during the interaction in the workplace while the government of Singapore has encouraged Singaporeans to speak grammatically correct English in formal settings such as workplaces. In this article, the researchers analyzed the conversation by describing tha grammar used in the Skype conversation. The data were collected from Skype chat history derived from daily conversation among the staffs of BSI and CMS. Then, the data were analyzed and described based on the grammatical characteristics of Singlish proposed by [1]. The findings reveal that the grammatical features of Singlish mostly appeared in the conversations were copula deletion, agreement, and the use of particles. In short, all participants fully utilized Singlish rather than SSE in discussing their work.AbstrakArtikel ini bertujuan untuk menyelidiki tata bahasa percakapan yang terjadi di antara staf PT. BSI dan Cocomas Singapore (CMS). Karena percakapan ini merupakan komunikasi lintas budaya, sebagian besar percakapan dilakukan melalui Skype. Staf CMS menggunakan Bahasa Inggris Singapura (Singlish) selama berinteraksi di tempat kerja sementara pemerintah Singapura telah mendorong warga Singapura untuk menggunakan bahasa Inggris yang benar secara tata bahasa dalam situasi formal seperti ditempat kerja. Pada artikel ini, para peneliti menganalisis percakapan dengan menjelaskan tata bahasa yang digunakan dalam percakapan Skype. Data dikumpulkan dari riwayat obrolan Skype yang berasal dari percakapan harian antara staf BSI dan CMS. Kemudian, data dianalisis dan disajikan berdasarkan karakteristik tata bahasa Singlish yang diusulkan oleh [1]. Temuan mengungkapkan bahwa fitur tata bahasa Singlish sebagian besar muncul dalam percakapan adalah penghapusan kopula, kesepakatan, dan penggunaan partikel. Singkatnya, semua peserta sepenuhnya menggunakan Singlish daripada SSE dalam mendiskusikan pekerjaan mereka.[1] Leimgruber (2011)[1] Leimgruber (2011)